The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/j.jhealeco.2004.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Information asymmetry, insurance, and the decision to hospitalize

Abstract: CIRANOLe CIRANO est un organisme sans but lucratif constitué en vertu de la Loi des compagnies du Québec. Résumé / AbstractÀ l'aide d'un modèle théorique dans lequel patients et médecins doivent choisir la quantité de service à utiliser ainsi que celui, de l'omnipraticien ou du spécialiste oeuvrant à l'hôpital, qui fournira ces services, nous analysons différents mécanismes d'incitation agissant sur l'offre et la demande. Nous étudions essentiellement deux modes d'organisation : le système conventionnel de ré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…The case of the non-splitter is similar to Blomqvist and Léger (2005) where patients perceive their health status within broad intervals, and as a result, primary care physicians have an incentive to understate severity, in order to prevent having to refer patients out to specialists. Moreover, the cutoff point for surgical risk chosen by both splitters and non-splitters exceeds the clinically desired one.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of the non-splitter is similar to Blomqvist and Léger (2005) where patients perceive their health status within broad intervals, and as a result, primary care physicians have an incentive to understate severity, in order to prevent having to refer patients out to specialists. Moreover, the cutoff point for surgical risk chosen by both splitters and non-splitters exceeds the clinically desired one.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Seminal work in this area has focused on demand inducement, where financial incentives may increase the quantity of services recommended and delivered by physicians beyond the point at which the medical benefits of such services justify their costs (Evans, 1974;McGuire and Pauly, 1991;Labelle et al, 1994;Gruber and Owings, 1996). Prior work on referrals by physicians for office-versus hospital-based care has highlighted the effects of financial incentives on decisions regarding the utilization of resources for the care of acute conditions (Marinoso and Jelovac, 2003;Blomqvist and Léger, 2005;Bain and Morrisey, 2007;David and Helmchen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies assessed the interaction between insurance and health services consumption as well as demand (26,33). Blomqvist and Leger in a study assessing the interaction between insurance and health services utilization, found out that in the context where the doctors were paid by capitation and patients who paid only part of the cost of their health services, the physician practice was significantly influenced by information asymmetry, patient cost sharing and fee-for-service payment method (26).…”
Section: Resultsmentioning
confidence: 99%
“…Blomqvist and Leger in a study assessing the interaction between insurance and health services utilization, found out that in the context where the doctors were paid by capitation and patients who paid only part of the cost of their health services, the physician practice was significantly influenced by information asymmetry, patient cost sharing and fee-for-service payment method (26). Dusansky, in a study, assessed the effects of the interaction between insurance choice and medical service demand and reported that an increase in price for medical services led to a decrease in the request for medical services and also an increase in the request for more insurance coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Confounding variables in different sites and spillover effects in the same sites leave most research inconclusive at best. (2)(3)(4)(5)(6) This article addresses the inefficiency of global capitation by comparing the operating characteristics of small and large insurers. Global capitation usually involves large risk-transferring entities (e.g., managed care organizations, insurers, Medicare, or Medicaid) passing insurance risks to many smaller insurance risk-assuming provider organizations, such as physician practices, hospitals, long-term care facilities, or home health agencies.…”
mentioning
confidence: 99%